The diagnosis of pleural effusions - Porcel, J; Azzopardi, M; Koegelenberg, C; Maldonado, F; Rahman, N; Lee, Y (Taylor and Francis, 2015)
© 2015 Taylor and Francis. Pleural effusions arise from a variety of systemic, inflammatory, infectious and malignant conditions. Their precise etiological diagnosis depends on a combination of medical history, physical examination, imaging tests and pertinent pleural fluid analyses; including specific biomarkers (e.g., natriuretic peptides for heart failure, adenosine deaminase for tuberculosis, or mesothelin for mesothelioma). Invasive procedures, such as pleuroscopic biopsies, may be required for persistently symptomatic effusions which remain undiagnosed after the analysis of one or more pleural fluid samples. However, whenever parietal pleural nodularity or thickening exist, image-guided biopsies should first be attempted. This review addresses the current diagnostic approach to pleural effusions secondary to heart failure, pneumonia, cancer, tuberculosis and other less frequent conditions.